Quelle archive pour les émotions littéraires ? Le cas de l’événement mille lectures d’hiver - Michèle Fontaine; Mathilde Roussigné (Itinéraires)
The mille lectures d'hiver festival and the archives generated by the event provide a privileged field to observe literary emotions, the multiplicity of their forms, their temporalities and their actors, but also the amplitude of their semantic field and the difficulty to seize and describe them. This paper comprises an interview with Michèle Fontaine who headed the project (2006-2022) and an excursion into the archives. It also seeks to provide methodological guidelines for an applied analysis of the archival traces of literary emotions.